Ultralong Oxford Nanopore Reads Enable the Development of a Reference-Grade Perennial Ryegrass Genome Assembly. (10th July 2021) - Frei, Daniel; Veekman, Elisabeth; Grogg, Daniel; Stoffel-Studer, Ingrid; Morishima, Aki; Shimizu-Inatsugi, Rie; Yates, Steven; Shimizu, Kentaro K; Frey, Jürg E; Studer, Bruno; Copetti, Dario
Abstract: Despite the progress made in DNA sequencing over the last decade, reconstructing telomere-to-telomere genome assemblies of large and repeat-rich eukaryotic genomes is still difficult. More accurate basecalls or longer reads could address this issue, but no current sequencing platform can provide both simultaneously. Perennial ryegrass ( Lolium perenne L.) is an example of an important species for which the lack of a reference genome assembly hindered a swift adoption of genomics-based methods into breeding programs. To fill this gap, we optimized the Oxford Nanopore Technologies' sequencing protocol, obtaining sequencing reads with an N50 of 62 kb—a very high value for a plant sample. The assembly of such reads produced a highly complete (2.3 of 2.7 Gb), correct (QV 45), and contiguous (contig N50 and N90 11.74 and 3.34 Mb, respectively) genome assembly. We show how read length was key in determining the assembly contiguity. Sequence annotation revealed the dominance of transposable elements and repeated sequences (81.6% of the assembly) and identified 38, 868 protein coding genes. Almost 90% of the bases could be anchored to seven pseudomolecules, providing the first high-quality haploid reference assembly for perennial ryegrass. This protocol will enable producing longer Oxford Nanopore Technology reads for more plant samples and ushering forage grasses into modern genomics-assisted breeding programs.